A Land Value Capture: Taxation and Value for Money Perspectives - Machfud Sidik (LPPM-STPI, 2021)
Providing basic services in urban areas effectively is one of the most significant challenges facing city governments, as the ability to provide urban services largely determines the competitiveness, poverty level and quality of life of urban residents. Metropolitan cities and big cities in Indonesia face various needs for urban infrastructure services, including a mass rapid transportation system to serve public transportation in the downtown area and hinterland areas. Urban local governments face the dilemma of limited funding in servicing the increasing demand for urban services, mainly due to the flow of urbanization and increasing urban services, including as a center for financial and digital transactions. Land Value Capture (LVC) is an alternative solution that must be developed by city governments in Indonesia, especially in the perspective of taxation and other forms of return on investment costs. Institutional strengthening, the collaboration between agencies, legal certainty, and robust regulations are the main prerequisites for implementing LVC in Indonesia